Small-molecule and peptide inhibitors of m6A regulators - Xiaocui Liu; Xiaocui Liu; Xiaocui Liu; Xuefeng Kan; Xuefeng Kan; Xuefeng Kan (Frontiers in Oncology)
N6-methyladenosine (m6A) is a reversible mRNA modification that plays important roles in malignant tumor processes. m6A modification has emerged as a significant research focus. Studies on the functions and mechanisms of m6A and its regulatory factors across various tumors have grown increasingly comprehensive and in-depth. Accumulating evidence has demonstrated that m6A modifications and their associated regulatory proteins can serve as biomarkers for cancer treatment and prognosis. Consequently, there has been a surge in research on the development and application of m6A regulatory factor inhibitors, particularly regarding their efficacy and mechanisms in tumor therapy. These advancements not only enhance the understanding of their therapeutic potential in diverse cancers but also facilitate their integration with existing treatments, accelerating the design of more effective, specific, and selective inhibitors. Such efforts hold promise for advancing m6A-targeted pharmaceutical development and promoting clinical applications. This review summarizes small-molecule and peptide inhibitors of m6A regulators for malignant tumors.